Cyril of Scythopolis on Relieving the Damage in Palestine Inflicted during the Samaritan Revolt (529–531) - Milewski, Ireneusz (Studia Ceranea, 2022)
The text analyses a short account by Cyril of Scythopolis concerning the imperial decision to finance the repair of the damages caused in Palestine by the Samaritan uprising of 529–531. A description of the alleged circumstances of this decision and information regarding the amount of the sum granted are examined. According to Cyril’s account, the granted sum, 13 centenarii of gold, was to be set aside from the tax revenues of Palestine and then used to rebuild (only) the ecclesiastical and monastic infrastructure. It is not clear from the text whether the repair of the aforementioned damage was to be financed only in the area of Palaestina secunda (where the main fighting of the rebellion took place) or also in Palaestina prima. Moreover, there is no mention in the text in question (as well as in other sources of the period) of the financing of the repair of other damages, which undoubtedly were also caused by the Samaritan uprising. The issue that interested the author most was the amount of money that the Emperor Justinian allegedly allocated for the above-mentioned purpose. In order to verify the amount, the author compared it with other data showing the abundance of the imperial treasury at the time of Anastasius and Justinian, as well as reached for other information on the wealth of the cities at that time. After analysing this data, the author has come to the conclusion that, despite some doubts, the sum of 13 centenarii of gold (1,300 pounds) mentioned by Cyril and allegedly allocated by the imperial court to repair the damage caused by the Samaritan uprising seems quite reasonable.